2020
DOI: 10.1101/2020.05.01.20087411
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Related Mortality: Is the BCG Vaccine Truly Effective?

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has become a worldwide emergency. In the attempt to search for interventions that would improve outcomes, some researchers have looked at the potential benefit of BCG vaccination. These early studies have found a statistically significant reduction in COVID-19 related mortality in countries with a current universal bacille Calmette-Guérin (BCG) vaccination policy; partially explained by induced heterologous immunity. However, just as the authors themselves noted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Finally, we use available data to explore a possible association between BCG vaccination and aggravated cases of COVID-19, and deaths [a relationship which is being investigated in some clinical trials (37)] 13 . The evidence is still inconclusive because the argued existence of uncontrolled confounders (38)(39)(40)(41)(42). However, if these confounders exist, they can bias the relationship between SARS-CoV-2 detections rates and the cumulative number of deaths.…”
Section: Regression Analysismentioning
confidence: 99%
“…Finally, we use available data to explore a possible association between BCG vaccination and aggravated cases of COVID-19, and deaths [a relationship which is being investigated in some clinical trials (37)] 13 . The evidence is still inconclusive because the argued existence of uncontrolled confounders (38)(39)(40)(41)(42). However, if these confounders exist, they can bias the relationship between SARS-CoV-2 detections rates and the cumulative number of deaths.…”
Section: Regression Analysismentioning
confidence: 99%
“…Paredes et al, showed that when confounders such as under-reporting, SARS-CoV-2 capability testing and differing lockdown measures were considered, the differential impact of BCG vaccination on COVID-19 related mortality rate was not significant (21). Among high-income countries, the mean number of deaths per 1 million population for countries with no universal BCG vaccination (223.2 ± 166.1) was not statistically significant from countries with current or previous BCG vaccination programs (55 ± 82.5; P = 0.85).…”
Section: The Bacille Calmette-guérin (Bcg) Vaccinementioning
confidence: 99%
“…Several ecological studies did suggest the potential protective effect of the universal BCG vaccination program on reducing COVID-19 morbidity and mortality [5][6][7][8][9][10][11][12][13]; some also implied that different BCG strains might vary in their protective ability [14]. In contrast, the inverse relation between COVID-19 disease burden and BCG vaccination was not observed by others [15,16]. However, these results are based on epidemiological data and have inherent biases [17,18].…”
Section: Introductionmentioning
confidence: 99%